Analisis Faktor yang Berpengaruh pada Kinerja Usaha Restoran dan Rumah Makan di Kota Malang - Setiawan, Margono (Jurnal Aplikasi Manajemen, 2008)
Restaurant business has grown and developed quickly from time to time. This development of restaurant business depends on competitiveness culture include : entrepreneurship, innovation, organizational learning and market orientation in restaurant business. Because of that, it is needed a good performance to increase restaurant services. The aim of this research is to analyze the significant effects among entrepreneurship, innovation, organizational learning and market orientation on restaurant business performance. And to analyze the dominant effects to restaurant business performance. This research was conducted to restaurant entrepreneur in Malang using purposive sampling method, with the sample of 144 respondents. The data were collected using questionnaires, observation and interview. The analytical tools used in this research to answer the research hypotheses was Confirmatory Factor Analysis (CFA), whereas, to detect the dominant effect using multiple regression analysis. The results of this research shows that: entrepreneurship and innovation factors have a positive effect to restaurant business performance. Whereas, marker orientation have negative effect and organizational learning have no significant effect to restaurant business performance. Among those four factor, innovation have dominant effect to restaurant business performance.